Ruta de aprendizaje de gestión del conocimiento en fundaciones empresariales (2019)
This article presents the design of a learning route for knowledge management in business foundations with intervention in the department of Valle del Cauca (Colombia). This route implies previously a conceptual clarity and an investigation to 11 foundations in front of the topic, to be able to establish its different phases of conformation, which involve the initial diagnosis of the knowledge (characterization of the current state), a mapping of this knowledge (identification of flow paths), the typification of the available human talent (human capital responsible for the management) and the mechanisms for the transfer of knowledge (involv-ing activities of identification, systematization, pro-cessing, storage and communication). The above with the intention of democratizing the existing knowledge in the relationship company-foundation-community and generate added value through the implementation of this type of methodologies, framed in the present k nowledge so ciety.